Effect of straw type (Cajnus cajan or Cicer arietinum) and form of diet on growth, feed efficiency and slaughter performance of weaned Jamunapari goat kids - SINGH, M K; TRIPATHI, M K; DIXIT, A K; SINGH, S K (The Indian Journal of Animal Sciences, 2016)
An experiment on Jamunapari goat kids (24), 90-day-old was carried out to assess the effect of straw type (arhar, Cajnus cajan or gram, Cicer arietinum) and form of diet (mash or pellet) on growth, feed efficiency and slaughtering performance. Slaughtering performance was assessed at 9 and 12 months age on 3 animals from each group. Two types of complete feed mixtures were prepared using straw and concentrate in 60:40 ratio. One part of each complete feed mixture was converted to pellet form of diet while another part remained as mash. These were randomly allocated to four groups of kids, six in each and fed ad lib. The kids under present feeding and management protocol attained live weight 18 to 19 kg at 6 month, 24 to 28 kg at 9 month and 31 to 34 kg at 12 month of age, with average daily gain (ADG) 71 to 84 g during entire growth period. The feed efficiency (kg feed / kg gain) ranged from 14.5 to 21.1 kg. The carcass weight at 9 month was 11.4 to 12.2 kg, whereas at 12 month varied from 15.0 to16.3 kg and the dressing percent ranged from 54 to 57. Growth, feed efficiency, carcass weight and dressing percent were similar among 4 kid groups and were not different between the 2 straws and diet forms. Study revealed that goats in general and Jamunapari breed in particular could be maintained under stall feeding with diets containing high proportion of crop residues (gram or arhar straw). The diets with roughage to concentrate ration 60:40 provided daily gain up to 84 g, with FCR 14 kg and live weight 34 kg at 12 months of age. Appropriate age of slaughter in Jamunapari kids was observed as 9 month because kids at this age have the greater FCR with low cost of feeding. Pellet diet has better economics for commercial kid production. Therefore, it is suggested that Jamunapari goat kids can be maintained under stall feeding conditions on crop residues based feeding systems suitable for rural as well as goat entrepreneur development under urban locations.